A comparison of SARS-CoV-2 RNA extraction with the QuickGene-810 Nucleic Acid Isolation System compared to the EZ1 Advanced DSP Virus Kit. Issue 5 (27th May 2022) - Phan, Thuy; Stephenson, Rebecca; Cai, Tina; Andacic, Nikol; McKew, Genevieve
Abstract : The QuickGene-810 Nucleic Acid Isolation System is a semi-automated extraction platform which may be used for RNA extraction. New methods were required to support the rapid increase in respiratory virus testing during the SARS-CoV-2 pandemic. The aim of this study was to assess SARS-CoV-2 RNA extraction using the QuickGene-810 kit compared to the EZ1 Advanced Extraction Platform for use on the AusDiagnostics SARS-CoV-2, Influenza and RSV 8-well RT-PCR assay. Qualitative results from all clinical samples were concordant between the QuickGene-810 and the EZ1 extraction methods, demonstrating that the QuickGene-810 kit is suitable for use in pathogen diagnostics. However, there was an average difference of approximately two cycles between the cycle threshold (Ct) values for both SARS-CoV-2 targets, suggesting that the EZ1 kit yields a higher concentration of nucleic acid extract, possibly related to its use of carrier RNA and/or smaller elution volume, which infers the possibility of false negative results for samples with very low viral loads.